Implementasi Undang-Undang No.18 Tahun 2013 Tentang Pencegahan Dan Pemberantasan Perusakan Hutan (Studi Kasus Tentang Faktor-Faktor Yang Mempengaruhi Masyarakat Melakukan Perambahan Hutan Di Desa Lunyuk Ode Kecamatan Lunyuk Kabupaten Sumbawa Besar) - Amil Amil; Taufik Rachman (Universitas Muhammadiyah Mataram, 2018)
One of the causes of forest destruction is forest encroachment. The problem of forest encroachment has become a national problem. Several factors have caused the community to do forest encroachment, namely weak law enforcement, income factors, education factors, the existence of sponsors and the limitations of forest supervision officers. Increasing the number of residents resulted in an increase in the need for land to share interests. This increasing need threatens the existence of forests. The increasing need for land has resulted in increased forest clearance. Problems related to forest encroachment in Lunyuk Ode Village, Lunyuk Subdistrict, Sumbawa Besar Regency have caused researchers to be interested in conducting research with the title